Lethal photosensitization and guided bone regeneration in treatment of peri-implantitis: an experimental study in dogs - Shibli, J. A.; Martins, M. C.; Ribeiro, F. S.; Garcia, V. G.; Nociti, F. H. (Blackwell Publishing, 2006)
The purpose of this study was to evaluate the effect of lethal photosensitization and guided bone regeneration (GBR) on the treatment of ligature-induced peri-implantitis in different implant surfaces. The treatment outcome was evaluated by clinical and histometric methods. A total of 40 dental implants with four different surface coatings (10 commercially pure titanium surface (cpTi); 10 titanium plasma-sprayed (TPS); 10 acid-etched surface; 10 surface-oxide sandblasted) were inserted into five mongrel dogs. After 3 months, the animals with ligature-induced peri-implantitis were subjected to surgical treatment using a split-mouth design. The controls were treated by debridment and GBR, while the test side received an additional therapy with photosensitization, using a GaAlAs diode laser, with a wavelength of 830 nm and a power output of 50 mW for 80 s (4 J/cm(2)), and sensitized toluidine blue O (100 mu g/ml). The animals were sacrificed 5 months after therapy. The control sites presented an earlier exposition of the membranes on all coating surfaces, while the test group presented a higher bone height gain. Re-osseointegration ranged between 41.9% for the cpTi surface and 31.19% for the TPS surface in the test sites; however differences were not achieved between the surfaces. The lethal photosensitization associated with GBR allowed for better re-osseointegration at the area adjacent to the peri-implant defect regardless of the implant surface.
Keywords: guided bone regeneration; histology; peri-implantitis; photodynamic therapy; photosensitizers; re-osseointegration